2005
DOI: 10.1158/1078-0432.ccr-05-0216
|View full text |Cite
|
Sign up to set email alerts
|

XAGE-1 Expression in Non–Small Cell Lung Cancer and Antibody Response in Patients

Abstract: Purpose: XAGE-1 was originally identified by the search for PAGE/GAGE-related genes using expressed sequence tag database and was shown to exhibit characteristics of cancer/testis-like antigens. Four transcript variants XAGE-1a, XAGE-1b, XAGE-1c, and XAGE-1d have been identified thus far.We recently identified XAGE-1b as a dominant antigen recognized by sera from lung adenocarcinoma patients.We here investigated the mRNA expression of four XAGE-1variants and XAGE-1protein expression in non^small cell lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 9 publications
5
69
0
Order By: Relevance
“…For example, antibodies to NY-ESO-1 are found in ≈50% of stage IV melanoma patients expressing NY-ESO-1 in their tumor, but the overall frequency in melanoma is about 8% when considering earlier stages (with less frequent NY-ESO-1 expression) and nonexpressing tumors (31). Similarly, p53 and XAGE-1 are immunogenic in 10-30% of non-small-cell lung cancers, depending on type and stage, but very rarely so in melanoma (35)(36)(37). Therefore, in the current study, the frequencies of seroreactivity observed against top antigens in pancreatic and ovarian cancer patients have to be placed in the context of cognate antigen expression frequency, tumor type selected, and stage.…”
Section: Discussionmentioning
confidence: 99%
“…For example, antibodies to NY-ESO-1 are found in ≈50% of stage IV melanoma patients expressing NY-ESO-1 in their tumor, but the overall frequency in melanoma is about 8% when considering earlier stages (with less frequent NY-ESO-1 expression) and nonexpressing tumors (31). Similarly, p53 and XAGE-1 are immunogenic in 10-30% of non-small-cell lung cancers, depending on type and stage, but very rarely so in melanoma (35)(36)(37). Therefore, in the current study, the frequencies of seroreactivity observed against top antigens in pancreatic and ovarian cancer patients have to be placed in the context of cognate antigen expression frequency, tumor type selected, and stage.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 We have shown similar antibody responses in patients with XAGE-1b-expressing lung cancer. 32 However, antibody responses were observed in less than 1% of patients against other CT antigens, e.g., MAGE-1. 26 Our study demonstrated the immunogenicity of CCDC62-2 by examining serum reactivity by ELISA using recombinant protein.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection with mRNA was shown to be able to present the antigen naturally to not only CD8 but also CD4 T cells (16,17,20). XAGE-1b mRNA was shown to be expressed frequently in non-small cell lung cancer (15/49, 31%), liver cancer (11/19, 58%), and prostate cancer (14/54, 24%), and less frequently in breast cancer (1/20, 5%) (12,18). In lung cancer, a high frequency of XAGE-1b mRNA expression was observed in adenocarcinoma (14/31, 45%) (18).…”
Section: Discussionmentioning
confidence: 99%
“…XAGE-1b mRNA was shown to be expressed frequently in non-small cell lung cancer (15/49, 31%), liver cancer (11/19, 58%), and prostate cancer (14/54, 24%), and less frequently in breast cancer (1/20, 5%) (12,18). In lung cancer, a high frequency of XAGE-1b mRNA expression was observed in adenocarcinoma (14/31, 45%) (18). XAGE-1b protein expression was observed immunohistochemically in most XAGE-1b mRNA-expressing lung cancers (18).…”
Section: Discussionmentioning
confidence: 99%